The LDI Enigma Part II: Indeterminate depth burns, man or machine?. Issue 8 (December 2021) - Claes, Karel E.Y.; Hoeksema, Henk; Robbens, Cedric; Verbelen, Jozef; Dhooghe, Nicolas; De Decker, Ignace; Monstrey, Stan
Highlights: More than half of the burn centers had more than 10 years of LDI experience. 89% of burn centers described LDI accuracy as mainly to almost completely accurate. IDB treatment depends on LDI colors, confounding and non-burn depth related factors. Intermediate depth burns versus indeterminate treatment burns. Recommendations are distilled for translating LDI colors into therapeutic decisions. Abstract: Introduction: Laser Doppler imaging is universally considered the most evidence-based method for objective burn depth assessment by accurately predicting burn wound healing potential. This study has analyzed how exactly laser Doppler imaging measurements can be useful in the early therapeutic decision making for patients with clinically indeterminate depth burns. Material and methods: An extensive survey, by questionnaire and in-depth interviews, was conducted among 51 burn centers worldwide to gain insight on the practical use of laser Doppler imaging. Results: Twenty-seven (53%) of the 51 burn centers contacted almost completely answered the 32 questions. Fifty-two percent of these centers (14/27) had at least 10 years of laser Doppler imaging experience. laser Doppler imaging was considered to be mainly or almost completely accurate by 89%. In case of discrepancy between clinical assessment and LDI, 41% relied more on clinical diagnosis, 25% delayed decision to operate, while 16% re-scanned the next day. The centers most experienced with laser Doppler imaging (13%) relied on it more. Final decisions for treatment were based on the combination of laser Doppler imaging and clinical assessment by 74%. Seventy percent of the centers almost never operated burns with laser Doppler imaging-red and would almost always operate burns with LDI-blue. Treatment decisions for intermediate laser Doppler imaging colors (pink, yellow and green) varied, with 76% basing decisions on other factors: % Total Body Surface Area (TBSA), general health, age, location of the burn, potential for colonization/infection, patient preference, compliance with aftercare, logistics, and socio-economic factors. Conclusion: Laser Doppler imaging reduces the number of clinical indeterminate depth burns. For these intermediate depth burns on laser Doppler imaging, treatment decisions are based on a combination of interpretation ('man') and laser Doppler imaging measurements ('machine'). Thorough knowledge of confounding factors and validated laser Doppler imaging color code, consideration of surrounding laser Doppler imaging colors, the use of mean flux values, and not directly burn related factors are essential. Burn centers with most laser Doppler imaging experience considered laser Doppler imaging an indispensable diagnostic tool.